The Validation of the 2023 ACR/EULAR Antiphospholipid Syndrome Classification Criteria in a Cohort from Turkey - Salim Mısırcı; Ali Ekin; Burcu Yağız; Belkıs Nihan Coşkun; Ediz Dalkılıç; Yavuz Pehlivan (Diagnostics)
Background/Objectives: Our aim was to validate the performance of the American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria for antiphospholipid syndrome (APS), published in 2023, in an APS cohort. Methods: A total of 193 patients, 83 with APS (secondary APS, n = 45; primary APS, n = 38) and 110 without APS (systemic lupus erythematosus (SLE), n = 100; others, n = 10), were included in this study. The performance (sensitivity, specificity and area under the curve (AUC)) of the 2023 ACR/EULAR classification criteria for APS was evaluated and the agreement with the revised Sapporo criteria was compared using the kappa test. Results: In our cohort, the sensitivity and specificity of the 2023 ACR/EULAR classification criteria for APS were 73% and 94%, respectively (AUC: 0.836, 95% CI: 0.772–0.899), while the sensitivity and specificity of the revised Sapporo criteria were 66% and 98%, respectively (95% CI: 0.756–0.888). The performance of the two sets of criteria in our cohort was significantly consistent and significant (p < 0.001). When the sensitivity, specificity and ROC curve analysis were performed again by excluding livedo racemosa, the sensitivity of the new criteria in our cohort was 62% and the specificity was 100% (AUC: 0.813, 95% CI: 0.746–0.881). Conclusions: Although the newly published criteria broaden the scope of APS classification by including clinical findings other than thrombosis and obstetric criteria, their sensitivity in our cohort was low. On the other hand, we found that the specificity of the criteria in our cohort reached 100% when livedo findings were excluded.